The Maintenance Location Choice Problem for railway rolling stock. (December 2021) - Zomer, Jordi; Bešinović, Nikola; de Weerdt, Mathijs M.; Goverde, Rob M.P.
Abstract: Due to increasing railway use, the capacity at railway yards and maintenance locations is becoming limiting to accommodate existing rolling stock. To reduce capacity issues at maintenance locations during nighttime, railway undertakings consider performing more daytime maintenance, but the choice at which locations personnel needs to be stationed for daytime maintenance is not straightforward. Among other things, it depends on the planned rolling stock circulation and the maintenance activities that need to be performed. This paper presents the Maintenance Location Choice Problem (MLCP ) and provides a Mixed Integer Linear Programming model for this problem. The model demonstrates that for a representative rolling stock circulation from The Netherlands Railways a substantial amount of maintenance activities can be performed during daytime. Also, it is shown that the location choice delivered by the model is robust under various time horizons and rolling stock circulations. Moreover, the running time for optimizing the model is considered acceptable for planning purposes. Highlights: Maintenance location choice problem keeping the planned rolling stock circulation. Automated method to assign maintenance activities to maintenance opportunities. Aims at moving maintenance to daytime to reduce capacity problems during nighttime. Advises on which maintenance locations to open during daytime and the work moved. Performance is demonstrated on real-life instances of the Dutch railway network.